Framing Public Opinion on Physician-Patient Conflicts on Microblog: A Comparative Content Analysis - Wanqi Gong; Qin Guo (Frontiers Media S.A., 2022)
IntroductionPhysician-patient conflicts in China have increased more than ten times from the 2000s to the 2020 and arouse heated discussions on microblog. The outbreak of the COVID-19 pandemic is believed to have brought a turnaround in the physician-patient relationship. However, little is known about the similarities and differences among the views of opinion leaders from the general public, physicians, and media regarding physician-patient conflict incidents on microblog, and whether the outbreak had an impact on this.ObjectiveThis study aims to explore how opinion leaders from the physicians, general public, and media framed posts on major physician-patient conflict incidents on microblog, and compare the microblog post frames before and after the COVID-19 pandemic. The findings will provide more objective evidence of the attitudes and perspectives of the health professionals, general public, and media on physician-patient conflicts, and the influence of pandemics on physician-patient relationship.MethodsA comparative content analysis was conducted to examine the posts (n = 941) of microblog opinion leaders regarding major physician-patient conflicts in China from 2012 to 2020.ResultsPost-pandemic microblog posts used more cooperation, positive and negative frames, but mentioned less health-related knowledge; no difference was found in the use of conflict and attribution frames. Results on the use of frames by opinion leaders from different communities found that the media used more conflict, cooperation, attribution, and positive frames, but used fewer negative frames and mentioned less health-related knowledge than general public and physicians. Results on the use of frames for different incidents found that incidents of violence against physicians used more cooperation, positive and negative frames and mentioned less health-related knowledge; in the contract, incidents of patient death used more attribution frames and mentioned more health-related knowledge.ConclusionThe physician and general public opinion leaders share some similarities in their post frames, implying that no fundamental discrepancy between them regarding physician-patient conflict incidents. However, the imbalanced use of frames by media microblogger would cultivate and reinforce the public perception of physician-patient contradictions. After the COVID-19 pandemic, more cooperation and positive frames were used in the posts, indicating an improvement in the physician-patient relationship in China.